ANALISIS KESIAPSIAGAAN RSUD dr. SOEDIRAN MANGUN SUMARSO WONOGIRI DALAM PENANGGULANGAN BENCANA - Arlisa Bayu Pratamaningtyas; Siswi Jayanti; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Disasters can happen anytime and anywhere no exception in hospital. dr. Soediran Mangun Sumarso hospital is a referral center top in Wonogiri district with lots of potential health hazards such as chemical factors, biological, ergonomics, physical and psychosocial. The number of potential hazards can cause an emergency or disaster so the hospital preparedness in disaster management is needed. This study aims to determine the preparedness dr. Soediran Mangun Sumarso hospital in disaster management. This research is qualitative in-depth interviews. The subjects included three members of occupational safety and health as key informants and four members, namely the hospital director, maintenance of facilities and infrastructure installation, chairman of the organization's health and safety, as well as the head of the civil service as an informant sub triangulation. Election of members of the organization of safety and health as key informants due to the three informants is a major implementation in disaster relief while the fourth election triangulation informant due to the fourth informant was responsible for each field. These results indicated that the hospital preparedness in disaster management hospital was still lacking because of the lack of coordination in disaster response organization, the absence of simulation that involves the whole of human resources, and lack of infrastructure related to disaster management. Therefore, it needs regular meetings to discuss matters related to disaster management, socialization Hospital Disaster Plan and simulations involving all the human resources, as well as the re-examination required infrastructure disaster management.